2023
DOI: 10.1093/hmg/ddad062
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cGAS-STING innate immune response in cells with deficient mitochondrial topoisomerase TOP1MT

Abstract: The recognition that cytosolic mtDNA activates cGAS-STING innate immune signaling has unlocked novel disease mechanisms. Here, an uncharacterized variant predicted to affect TOP1MT function, P193L, was discovered in a family with multiple early-onset autoimmune diseases, including Systemic Lupus Erythematosus (SLE). Although there was no previous genetic association between TOP1MT and autoimmune disease, the role of TOP1MT as a regulator of mtDNA led us to investigate whether TOP1MT could mediate the release o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…The TFAM paradigm suggested that other forms of mtDNA stress might also lead to mtDNA-release-mediated cGAS–STING signaling, which has turned out to be the case. Cells either lacking TOP1MT (EC 5.6.2.1) or expressing a pathogenic variant associated with lupus exhibit mtDNA release and activation of the cGAS–STING pathway ( 73 ). TOP1MT knockout cells have reduced mtDNA copy number and mitochondrial transcripts, defects in nucleoid organization, elongated mitochondria, and lower OXPHOS.…”
Section: Mitochondrial Dna Release-mediated Innate Immune Signalingmentioning
confidence: 99%
“…The TFAM paradigm suggested that other forms of mtDNA stress might also lead to mtDNA-release-mediated cGAS–STING signaling, which has turned out to be the case. Cells either lacking TOP1MT (EC 5.6.2.1) or expressing a pathogenic variant associated with lupus exhibit mtDNA release and activation of the cGAS–STING pathway ( 73 ). TOP1MT knockout cells have reduced mtDNA copy number and mitochondrial transcripts, defects in nucleoid organization, elongated mitochondria, and lower OXPHOS.…”
Section: Mitochondrial Dna Release-mediated Innate Immune Signalingmentioning
confidence: 99%
“…In addition, our method is robust enough to not only measure total levels of mtDNA for synthesis and turnover, but also separate linear, supercoiled and relaxed forms of mtDNA for subsequent quantification and analysis. As a result, our protocols allow for pinpointing the molecular mechanisms underlying changes in mtDNA copy number, as we have shown in models of mitochondrial dysfunction such as loss of TOP1MT 1,2 , or reduced TFAM expression 3 .…”
Section: Introductionmentioning
confidence: 94%
“…Here we describe a protocol that selectively incorporates bromodeoxyuridine into mtDNA for the measurement of mtDNA turnover, synthesis or supercoiling via an adapted immunoblot and Southern blot protocol. For complete use and execution of this protocol see Al Khatib et al 1,2 and Lei et al 3…”
mentioning
confidence: 99%
“…Furthermore, an increasing body of research has indicated that aberrant activation of the cGAS-STING pathway can lead to excessive and sustained production of inflammatory factors, including type I IFNs, contributing to the development of various diseases (74). The undeniable role of the cGAS-STING signaling pathway in innate immune diseases is supported by Al Khatib et al, who demonstrated that TOP1MT influences the activation of the mtDNA-mediated cGAS-STING innate immune response, and that the P193L variant may contribute to the autoimmune phenotype observed in patients (75). The inflammatory response induced by activation of the cGAS-STING signaling pathway is a significant factor in the progression of pulmonary fibrosis.…”
Section: Inhibitors Of Unknown Mechanismsmentioning
confidence: 99%